akuntansi aset tetap; PSAK no.16 ANALISIS PENERAPAN PSAK No.16 TERHADAP PERLAKUAN ASSET TETAP PADA BP BATAM - Natasha, Adinda; Khadijah, Khadijah (LPPM Universitas Putera Batam, 2022)
Batam is an special economic zone, which all land and assets in Batam City belong to the central goverment which are registered as property of the Ministry of Finance which is entrusted to managed by BP Batam. Fixed assets recorded as assets owned by BP Batam Hospital Business Entity are pasrt of BMN (State Owned Goods). Fixed assets are a fundamental part of every company or govermen, therefore it is necesary to have a clear recordof the fixed assets owned by BP Batam Hospital Business Entity. Therefore, planing and supervision are need which follow the aplication recording standar in Indonesia Financial Accounting Standar No.16 relating to acquisition, measurement, depreciation, termination, and disclosure of fixed assets. The main purepose of this study is to analyze the suitability of the accounting treatment of fixed assets owned by BP Batam Hospital Business Entity with the Statement of Financial Accounting Standard No.16, as well as the data colection method in study using interviews, literature studies, and documentation and using desciptive qualitatif data analysis techniques so that obtained a clear overview of the social situation, facts, nature, and the relationship between the investigated phenomena related of the accounting treatment of fixed assets. The results of the researc can concluded that BP’s Batam Enterprises Hospital Batam has recorded owned fixed assets in accordance with Statement of Financial Accounting Standard (IAS) No.16 and declarated to have complied with applicable financial accounting standards.